2024
DOI: 10.3390/rs16050796
|View full text |Cite
|
Sign up to set email alerts
|

Water Stress Index and Stomatal Conductance under Different Irrigation Regimes with Thermal Sensors in Rice Fields on the Northern Coast of Peru

Lia Ramos-Fernández,
Maria Gonzales-Quiquia,
José Huanuqueño-Murillo
et al.

Abstract: In the face of the climate change crisis, the increase in air temperature negatively impacts rice crop productivity due to stress from water scarcity. The objective of this study was to determine the rice crop water stress index (CWSI) and stomatal conductance (Gs) under different irrigation regimes, specifically continuous flood irrigation treatments (CF) and irrigations with alternating wetting and drying (AWD) at water levels of 5 cm, 10 cm, and 20 cm below the soil surface (AWD5, AWD10, and AWD20) in an ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
(49 reference statements)
0
1
0
Order By: Relevance
“…There is a good negative correlation between the CWSI and photosynthetic parameters [ 6 , 10 ]. The results of Ramos-Fernández et al [ 11 ] showed a strong correlation between the CWSI and gs (R 2 = 0.91). When the crop is subjected to water stress, the soil–root hydraulic resistance increases [ 12 ], which reduces root water transport and eventually leads to the reduction in or closure of plant stomata and a decrease in photosynthetic parameters [ 13 ].…”
Section: Introductionmentioning
confidence: 96%
“…There is a good negative correlation between the CWSI and photosynthetic parameters [ 6 , 10 ]. The results of Ramos-Fernández et al [ 11 ] showed a strong correlation between the CWSI and gs (R 2 = 0.91). When the crop is subjected to water stress, the soil–root hydraulic resistance increases [ 12 ], which reduces root water transport and eventually leads to the reduction in or closure of plant stomata and a decrease in photosynthetic parameters [ 13 ].…”
Section: Introductionmentioning
confidence: 96%